DIAGNOSIS OF POTATO VIRUSES IN KAZAKHSTAN: MOLECULAR CHARACTERISATION OF ISOLATES - Karpova , O.V.; Alexandrova , A.M.; Nargilova , R.M.; Kryldakov , R.V.; Yekaterinskaya , E.M.; Romadanova , N.V.; Kushnarenko , S.V.; Iskakov , B.K. (Eurasian Journal of Applied Biotechnology, 2019)
Virus infection is one of the reasons for the low potato yield in Kazakhstan. The combination of modern methods of germplasm improvement and effective virus diagnosis are the most successful measures to overcome potato viruses. Using ELISA and multiplex RT-PCR methods, potato leaf samples from the Almaty and Kostanay regions of Kazakhstan were analysed for the presence of the carlaviruses potato virus M and potato virus S, the potyvirus potato virus Y, the potexvirus potato virus X, and the polerovirus potato leaf roll virus (PVM, PVS, PVY, PVX, and PLRV, respectively). The potato virus spectrum has changed over the last twenty years, and presently carlavirusеs represent the most widespread genus. Of the leaf samples tested, 84.3% and 46.6% were infected by PVM and PVS, respectively, and co-infection by both viruses occurred. Multiplex RT-PCR assays were developed to detect the five potato viruses, and for two strains of PVS. Based on sequence analyses of the central region of the capsid protein, fourteen Kazakh PVS isolates were identified, of which eleven were classified as the ‘ordinary’ strain, and three as ‘Andean’ strains. Our findings confirmed the existence of divergent PVS strains with different origins present in Kazakhstan.